A user perspective on errors-in-variables methods in system identification. (August 2019) - Söderström, Torsten
Abstract: The paper starts with a brief survey of errors-in-variables methods in system identification. Background and motivation are given, and it is illustrated why the identification problem can be difficult. Under general weak assumptions, the system is not identifiable, but can be parameterized using one degree of freedom. Examples where identifiability is achieved under additional assumptions are also provided. A number of approaches for parameter estimation of errors-in-variables models are reviewed. The underlying assumptions and principles for each approach are highlighted. The paper then continues by discussing from a user's perspective on how to proceed when practical problems are handled. Highlights: An overview of errors-in-variables methods for system identification is given. Common methods for errors-in-variables problems are reviewed. The role of underlying assumptions is discussed when dealing with practical applications. Theory can give useful guidelines when handling errors-in-variables problems in practice.